Beauty Technology: Designing Seamless Interfaces for Wearable Computing - Vega, Katia (Human–Computer Interaction Series, 2016)
The increasing advances in electronics allows smaller and more powerful devices, bringing wearable computing closer to reality. However, most wearable computers are very distinguished and placed on clothes and accessories. This book tries to tackle this phenomenon by introducing a new wearable computing subfield called beauty technology. By using the body's surface as an interactive platform, the integration of technology into beauty products is explored and can be applied directly to ones skin, fingernails, and hair adding new functionality to beauty products using technology in a personal, seamless and fashionable way. An interdisciplinary approach is taken, exploring the design of Beauty Technologies such as Conductive Makeup, Tech Nails, Hairware and FX e-makeup in order to create novel interfaces for Human Computer Interaction.